Implementasi Pembelajaran Fikih di MA Salafiyah Simbangkulon Pekalongan (Studi Komparasi Buku Ajar dan Kitab Kuning) - Putri Chaerusani; Bustanul Arifin (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to examine the implementation of fiqh learning in Islamic senior high schools (Madrasah Aliyah) by highlighting the differences between the use of official textbooks issued by the Ministry of Religious Affairs and traditional kitab kuning as learning resources. The focus of the study is directed toward effectiveness, students’ comprehension of learning materials, and the internalization of fiqh values within instructional practices. This research employs a qualitative approach using a comparative case study method in two Madrasah Aliyah that adopt different approaches: one utilizes modern fiqh textbooks, while the other employs the classical kitab kuning, particularly Taqrib. Data collection techniques include observation, in-depth interviews with the vice principal of curriculum affairs, fiqh teachers, Taqrib instructors, and analysis of learning documents. The findings indicate that: (1) the planning of fiqh learning using textbooks and kitab kuning is generally similar, although the use of kitab kuning is integrated with specific madrasah policies; (2) the implementation of learning shares several similar methods, yet distinctive pesantren-based methods and strategies are applied in fiqh learning using kitab kuning; and (3) the evaluation system shows similarities through written tests, alongside pesantren-style evaluations in kitab kuning-based fiqh learning. The results demonstrate that the use of kitab kuning tends to deepen classical fiqh understanding and foster critical analytical skills, while textbooks provide a more systematic structure aligned with the national curriculum but are less comprehensive in contextualizing Islamic legal principles. In conclusion, the integration of both learning resources can serve as an ideal solution to improve the quality of fiqh learning in madrasah. This study recommends the provision of teacher training in managing kitab kuning-based instruction methodologically so that it remains relevant to the needs of the modern curriculum.